2022
DOI: 10.3389/fnut.2022.844413
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Food Choices Among the Urban Indian Middle-Class: A Qualitative Study

Abstract: One of the leading risk factors for an escalating obesity burden in India is non-nutritious choices. Underpinned by the nutrition transition theory, this qualitative inquiry was designed to understand the urban middle-class Indian consumers’ views about processed foods and rapidly changing food choices. The study consisted of two phases, the first phase consisted of focus group discussions pertaining to the definition and conception of processed foods and the second phase consisted of interviews regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…A similar study from China has reported a lesser frequency of eating out [ 44 ]. With rapid economic developments, dietary patterns have changed, and eating out is the more acceptable culture in India [ 29 31 ]. Moreover, with the ease in the restrictions imposed during the COVID-19 pandemic, eating out has been even more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study from China has reported a lesser frequency of eating out [ 44 ]. With rapid economic developments, dietary patterns have changed, and eating out is the more acceptable culture in India [ 29 31 ]. Moreover, with the ease in the restrictions imposed during the COVID-19 pandemic, eating out has been even more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were offered the opportunity to ask questions on any issue which they did not understand and clarifications were provided. Each student completed their questionnaire within ten (10) to fifteen (15) minutes and returned it to a team of data collectors. Non-response rate was zero percent.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…The choices and intake of processed foods can be induced by factors such as changes in the food environment and variations in the socio-cultural setting [15]. Changes in the food environment include food advertisements and convenience, increased availability and accessibility of processed foods, replacement of traditional diet with Western food, foods as indicators of status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Be prepared to deal with the introduction of dietary risk factors/habits from outside of India (processed, packaged, and non-nutritious foods), which can contribute to obesity, which in itself is a significant risk factor for cancer. Identify and address/modulate socio-cultural factors that increase the impact of dietary risk factors such as urbanization, long work hours, transition to western diets that replace home-cooked Indian diet, and perceptions of an elevated status related to consumption of processed food [ 29 ]. Address and tackle the social taboos associated with the diagnosis of cancer [ 30 , 31 ].…”
mentioning
confidence: 99%